Daza Villar, Vladimir. Otros rostros de Caldas. Manizales: Editorial Universidad de Caldas, 2012 - López Castrillón, Hector Miguel (Historia Caribe, 2013)
Daza Villar, Vladimir. Otros rostros de Caldas. Manizales: Editorial Universidad de Caldas, 2012